Implementation of The MSME Empowerment Program Supervision System at The Infaq Management Foundation - Syamsiyah, Syamsiyah; Choiri, Muttaqin (Institut Agama Islam Negeri Ponorogo, 2022)
Zakat holds a very strategic position regarding religious, social, economic, and social welfare aspects. In terms of community welfare, three pillars must be optimized, one of which is the empowerment of zakat potential. To optimize zakat management, the government must perform a practical regulatory and supervisory function, which BAZNAS does at all levels. The potential of ZIS funds contributes to the expansion of MSMEs as a driver of economic growth. MSMEs require not only capital but also business advice. In Indonesia, zakat management institutions have funds that can be used for business capital or productive Zakat. However, numerous cases in Indonesia involve the mismanagement of productive zakat funds, one of which is the philanthropic organization Aksi Cepat Tanggap (ACT), which has recently come under scrutiny for cases of misappropriation of people's funds. The purpose of this research is to determine how the monitoring system for the UMKM empowerment program at the Infaq Management Institute (LMI) in Bangkalan Regency complies with Law No. 23 of 2011 on Zakat Management. As a result, it is necessary to investigate how the monitoring system for the MSME empowerment program is implemented at the LMI Bangkalan Branch. This study used a qualitative data collection approach, employing interviews, observation, and documentation studies. According to the findings of this study, the supervision of LMI Bangkalan takes the form of an annual report on the performance of LAZNAS LMI activities in the form of a Financial Audit. Supervision is carried out internally at the Bangkalan Branch LMI by holding weekly and monthly evaluation meetings in each field and external supervision from the East Java Central LMI and the Central BAZNAS.